DNAJA1 controls the fate of misfolded mutant p53 through the mevalonate pathway - Parrales, Alejandro (Nat Cell Biol, 2016)
Stabilization of mutant p53 (mutp53) in tumours greatly contributes to malignant progression. However, little is known about the underlying mechanisms and therapeutic approaches to destabilize mutp53. Here, through high-throughput screening we identify statins, cholesterol-lowering drugs, as degradation inducers for conformational or misfolded p53 mutants with minimal effects on wild-type p53 (wtp53) and DNA contact mutants. Statins preferentially suppress mutp53-expressing cancer cell growth. Specific reduction of mevalonate-5-phosphate by statins or mevalonate kinase knockdown induces CHIP ubiquitin ligase-mediated nuclear export, ubiquitylation, and degradation of mutp53 by impairing interaction of mutp53 with DNAJA1, a Hsp40 family member. Knockdown of DNAJA1 also induces CHIP-mediated mutp53 degradation, while its overexpression antagonizes statin-induced mutp53 degradation. Our study reveals that DNAJA1 controls the fate of misfolded mutp53, provides insights into potential strategies to deplete mutp53 through the mevalonate pathway–DNAJA1 axis, and highlights the significance of p53 status in impacting statins’ efficacy on cancer therapy.